The role of innovative building technologies in self-build architecture to facilitate sustainable human development in the informal housing context of South Africa - Van Reenen, Coralie (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--Univeristy of Pretoria, 2023.